Lone mothers’ time allocations: Choices and satisfactions - Le, Anh; Miller, Paul (Australian Council of Social Service, 2013)
This paper uses the 2006 Australian Time Use Survey to examine theallocation of time to personal care, employment-related activities, homeduties, leisure and child care of lone mothers, in comparison to the timeallocations of single women, women in childless couples and partneredmothers. Both primary and secondary time allocations are considered. Thesatisfactions that women report concerning their current time allocations arealso analysed. The time use and satisfaction data are described using bothtabulations and multiple regression methods. Lone mothers are shown tohave similar time allocations as the other types of households, even thoughthey have different financial and time resources. This raises the concernthat lone mothers’ desire or need to maintain such time allocations maylead to task overload. Consistent with this, lone mothers are found to beless satisfied with the way they allocate their time than single women andpartnered mothers. The tensions associated with time use among lonemothers discussed in the literature are real, and important.